'You gotta have something to chew on': perceptions of stress-induced eating and weight gain among office workers in South Korea. Issue 3 (19th February 2021) - Park, Sohyun; Sung, Eunju
Abstract: Objective: Job-related chronic stress has been discussed as a risk factor for weight change and metabolic disorders. The current study was conducted to understand the situations in which stress-induced eating occurs among office workers and how workers perceive stress to influence their daily eating practices and weight change. Design: In-depth, one-on-one interviews were conducted with office workers. Setting: Metropolitan areas in South Korea. Participants: Twenty-two office workers from thirteen companies participated in the study. Results: Most participants mentioned that they often felt work-related stress and reported various levels of perceived stress, as measured with open-ended questions. The main sources of work stress were (i) the nature of job characteristics, (ii) performance evaluations and (iii) relationships within the organisation. Participants linked stress with increased food consumption and cravings for sweet, savoury and greasy foods. Many participants emphasised the links between multiple health behaviours and stress. Not only dietary choices but also alcohol consumption, sleeping difficulty and insufficient physical activity were related to coping with work stress and demands. Finally, most participants who perceived work stress believed that their weight gain in adulthood was triggered by work stress. Conclusions: It is necessary to consider promoting behavioural modifications to support weight management and providing a means for stress management and the minimisation of stress-inducing working environments for workers to maintain or achieve a healthy weight and to prevent chronic disease incidence.